Kualitas Kinerja Operasional Karyawan di Provinsi DKI Jakarta pada Kondisi Pandemi Covid-19 (Studi pada Karyawan Tetap Sektor Perbankan di Provinsi DKI Jakarta yang Bekerja Operasional Secara Hibrida atau Jarak Jauh) - Argakoesoemah, Mohamad Ramadhan; Pracoyo, Antyo (STIE Indonesia Banking School, 2023)
This study aims to identify the influence of communication, organizational culture, and work from home on the performance of permanent employees in the banking sector in DKI Jakarta who work operationally in a hybrid or remotely during the Covid-19 pandemic conditions. The independent variables in this study are Communication, Organizational Culture, and Work from Home. While the dependent variable in this study is Employee Performance. Hypothesis testing in this study uses the SEM (Structural Equation Modeling) method, which is supported by IBM SPSS AMOS 22 and IBM SPSS Statistics 26 application devices. The data collection technique in this study used an online questionnaire with the Google Form application to collect information on respondents, who were permanent employees in the banking sector in DKI Jakarta who work operationally hybrid or remotely during the Covid-19 pandemic conditions. The results of this study indicate that: 1) Communication has a positive and significant effect on Employee Performance; 2) Organizational Culture does not have an effect on Employee Performance; 3) Work from Home does not have an effect on Employee Performance.